The Effect of Information Technology Infrastructure and the Internet of Things on Defense Industry Management Information Systems - Wasserbauer, Michal (Dinasti Publisher, 2022)
The article Literature Review the Effect of Information Technology Infrastructure and the Internet of Things on Defense Industry Management Information Systems is a literature review scientific article. The purpose of this article is to build a hypothesis of the influence or role between variables that will be used in future research, within the scope of management information systems science. The method of writing articles is a library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are: 1) Information technology infrastructure affects the defense industry management information system partially; 2) The Internet of things affects the defense industry management information system partially; and 3) Information technology infrastructure and the internet of things have a partial effect on the defense industry management information system. Apart from these 2 exogen variables that affect the endogenous variables of the defense industry driver's license, there are still other factors including employee capability, encryption and employee education.